Socio-demographic Characteristics and Visual Acuity Patients Underwent Cataract Surgery at Pandaan Eye Clinic: Poster Presentation - Observational Research - General practitioner - Medicarizky, Aulia; Wahyuni, Indri (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objective : Cataracts are one of the leading causes of blindness affecting 94 million worldwide including 77,7% blindness of Indonesians with prevalence in people aged over 50 years reaching 1,9%. This study aimed to describe the socio-demographic characteristics and visual acuity of patients who underwent phacoemulsification cataract surgery at Pandaan Eye Clinic. Methods : Patients were consecutively included from January 2022 to December 2022. Data of age, gender, area of residence, occupation, comorbid systemic disease, laterality, intraocular lens (IOL) power, and best-corrected visual acuity (BCVA) after four weeks of surgery was obtained. Visual acuity (VA) is classified in the WHO category. Data were recorded in sheets and proceeded using SPSS. Results : There were 1583 eyes out of 1230 patients with 55,4% having done unilateral cataract surgery and the most used IOL power at the range 19.00 to 23.00D (75%). The mean age was 60,83 ? 9,05 years and 53,9% were male. Most of them live in Pasuruan Regency (77,7%), without systemic comorbidity (68,8%), and work outdoors (62,2%). Before cataract surgery, most of the patients had blindness (57,6%) (presenting VA <3/60). The BCVA outcomes were 6/6 to 6/18 in 1129 eyes (71,3%). Conclusion : This study marked the immense incidence of cataracts as a cause of blindness, particularly in males. The increase in cataract surgery performed also determines that eye care services reach a certain area. Therefore, eye health resources must be evenly available throughout the country to reduce the impact of socio-demographic status